Analysis of the Ser Pilo Paga program, as a strategy to reduce the gap in Higher Education in Colombia (2020)
Abstract In Colombia higher education is governed by the provisions of the Political Constitution and regulated by Law 30 of 1992, under these guidelines the state has constantly sought to reduce the existing gap in access to higher education through strategies and programs that achieve a better educated country. Public policies in this matter have been established as a key element to guarantee the population with low economic resources access to quality higher education through strategies for their stay in accredited institutions, such as the Ser Pilo Paga program, which was implemented in 2014 by the government of former President Juan Manuel Santos to increase access rates to higher education.